2021
DOI: 10.3390/ijerph18031010
|View full text |Cite
|
Sign up to set email alerts
|

Young Swimmers’ Middle-Distance Performance Variation within a Training Season

Abstract: The current study aimed to longitudinally evaluate anthropometric, physiological, and biomechanical variables related to middle-distance performance during a 45-week swimming training season. Thirty-four swimmers (age: 12.07 ± 1.14 years) performed a maximum of 400 m front crawl at the beginning (T1) and finish of the first macrocycle (T2, 15 weeks) and the finish of the second (T3, 18 weeks) and third macrocycles (T4, 12 weeks). Time-related variables, stroke rate (SR), stroke length (SL), and stroke index (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 27 publications
1
7
0
1
Order By: Relevance
“…Nevertheless, SI (efficiency) was the best predictor of all the variables assessed (Lätt et al, 2009a , b ), or the one that presented the highest correlation with performance (Ferreira et al, 2019 ). Additionally, it was suggested that the 400-m freestyle enhancement during a season was highly related to an increase in the SI, suggesting that, when swimmers are in this age group, coaches should prioritize technical development of the swimmers (Ferreira et al, 2021 ). That said, the authors indicated that, concurrently, with the technical enhancement, physiological variables are as important to optimize swimming performance in such middle-distance events (Ferreira et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, SI (efficiency) was the best predictor of all the variables assessed (Lätt et al, 2009a , b ), or the one that presented the highest correlation with performance (Ferreira et al, 2019 ). Additionally, it was suggested that the 400-m freestyle enhancement during a season was highly related to an increase in the SI, suggesting that, when swimmers are in this age group, coaches should prioritize technical development of the swimmers (Ferreira et al, 2021 ). That said, the authors indicated that, concurrently, with the technical enhancement, physiological variables are as important to optimize swimming performance in such middle-distance events (Ferreira et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it was suggested that the 400-m freestyle enhancement during a season was highly related to an increase in the SI, suggesting that, when swimmers are in this age group, coaches should prioritize technical development of the swimmers (Ferreira et al, 2021 ). That said, the authors indicated that, concurrently, with the technical enhancement, physiological variables are as important to optimize swimming performance in such middle-distance events (Ferreira et al, 2021 ). Thus, at early ages, training should focus on learning the proper swimming techniques (i.e., technical training).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to other studies monitoring swimmers' performance that focused mainly on either overall performance or free-swimming phase parameters (Morais et al, 2013(Morais et al, , 2015, our proposed goal metrics allow the coach to track swimming performance in each phase separately. Furthermore, tracking progress using conventional methods such as video-based systems or heart rate and lactate monitors is very time-consuming and only possible at selected times during a season (Ferreira et al, 2021), whereas IMUs have the least impact on swimmers' training and can be used on a daily basis.…”
Section: δPushmentioning
confidence: 99%
“…They mostly rely on observation and personal experience to monitor and evaluate a swimmer’s performance. A coach expects swimmers to improve their performance by 1%–10% during a training season, depending on swimmer’s level ( Zacca et al, 2020 ; Ferreira et al, 2021 ), and usually tracks this progress by measuring lap time over different swimming distances (most commonly 400 m, as it is used to evaluate the swimmer’s aerobic performance). However, lap time can only reflect the swimmer’s overall progress and not their phase-based performance.…”
Section: Introductionmentioning
confidence: 99%
“…La búsqueda constante para alcanzar logros significativos (González et al, 2005), ya sean deportivos o formativos, hace que el entrenamiento deportivo sea pensado y repensado desde cada una de las variantes posibles de mejora o de desarrollo, por lo tanto, algunas disciplinas deportivas como es el caso de la natación carreras deben iniciar con sus procesos de entrenamiento desde edades tempranas. Debido a este tipo de consideraciones es necesario identificar con detalle cuales son los mejores mecanismos que permitan controlar las cargas de entrenamiento, en especial en edades infantiles y aminorar el riesgo de provocar lesiones derivadas de inadecuados procesos de planificación (Fröhner, 2003;Ferreira, et al, 2021). Los técnicos y entrenadores de este deporte se han encontrado a lo largo del tiempo con varias dificultades respecto al uso de herra-mientas que les permita programar y valorar con claridad las capacidades físicas de los deportistas, en el caso específico de este texto de la resistencia y la velocidad.…”
Section: Introductionunclassified